Mutational profile, outcomes, and impact of allogeneic hematopoietic stem cell transplantation in adult patients with acute myeloid leukemia and inconclusive cytogenetic analysis. (16th February 2023) - Vasudevan Nampoothiri, Ram; Tang, Kenny; Schuh, Andre; Lam, Wilson; Maze, Dawn; Michelis, Fotios V.; Chan, Steven; Gupta, Vikas; Kim, Dennis; Kumar, Rajat; Lipton, Jeffrey Howard; Mattsson, Jonas; et al.
Abstract: Background: Inconclusive cytogenetic analysis (IC) at baseline has been reported as a predictor of poor prognosis in patients with acute myeloid leukemia (AML). The mutational profile in this group of patients, and its impact on outcomes have not been reported. Methods: We retrospectively analyzed adult patients (≥18 years) with newly diagnosed AML treated with intensive induction chemotherapy between 2015 and 2019. Patients with any documented cytogenetic abnormalities were excluded. Targeted next generation sequencing (NGS) was performed in all patients. Baseline characteristics, mutation profile, and outcomes were compared between patients with normal cytogenetics(NC) and those with IC. Results: Sixty‐one patients (males 39.3%; median age 59 years) had IC at diagnosis. The proportion of patients with mutations in genes with proven prognostic impact were not different between AML patients with IC and NC. AML patients with NC were more likely to harbor the prognostically favorable NPM1 mut / FLT3‐ITD wt mutational combination conferring "favorable" risk status. As a result, a larger proportion of patients in the IC group underwent allogeneic hematopoietic stem cell transplantation (allo HCT; 54.1% vs. 39.6%; p  = .02). The 2‐year RFS (55.9% vs. 58.5%; p  = .29) and OS (61.9% vs. 66.9%; p  = .48) were similar in IC and NC patients. There was no difference in survival of patients who underwent allo HCT when compared with patients who did not ( p  = .99). Conclusions: Inconclusive cytogenetic analysis may not be an independent prognostic indicator in AML. In such patients, molecular abnormalities detected through NGS or whole genome sequencing are more likely to be informative.